Should we include avoidance of deforestation in the international response to climate change? - Schlamadinger, B.; Ciccarese, L.; Dutschke, M.; Fearnside, P.M.; Brown, S.; Murdiyarso, Daniel (Center for International Forestry Research, 2005)
Global deforestation and forest degradation rates have a significant impact on the accumulation of greenhouse gases (GHG) in the atmosphere. The Food and Agriculture Organization estimated that during the 1990s 16.1 million hectares per year were affected by deforestation, most of them in the tropics. The Intergovernmental Panel on Climate Change (IPCC) calculated that, for the same period, the contribution of land use changes to GHG accumulation into the atmosphere was 1.6±0.8 Gigatonnes of carbon per year, a quantity that corresponds to 25% of the total annual global emissions of greenhouse gases. Under the Kyoto Protoco (KP), industrialized countries can use land-based activities, such as reducing deforestation, establishing new forests (afforestation and reforestation) and other vegetation types, managing agricultural and forestlands in a way that the “carbon sink” is maximized. Annex I countries may also claim credit for carbon sequestration in developing countries by afforestation and reforestation (AR) through the Clean Development Mechanism (CDM), one of the Kyoto Mechanisms that allow countries to achieve reductions where it is economically efficient to do so. For the period 2008-12, forestry activities under the CDM have been restricted to afforestation and reforestation on areas that were not forested in 1990. In contrast, activities aimed at reversing or slowing deforestation in developing countries are excluded for the first commitment period of the KP (2008-2012). Recently, a new proposal to include deforestation avoidance in tropical countries, labelled “compensated reduction,” has been presented by researchers from Brazil. This paper discusses the pros and cons of the approach, and provides an assessment of the approach with respect to leakage, non-permanence, forest degradation, uncertainties of baseline estimates, incentives to improve land use, and scale of credits. The paper also presents some suggested refinements and addresses monitoring needs. According to the community, climate change is not a special phenomenon and they are not aware of it. Climate change is therefore explained by linking it to their environment, such as fish that are becoming more rare, the fact that they have further to go to get timber, changes in agriculture crop planting season, and similar things. The constraints arise perhaps because community education levels are quite low, the project has different interests than some community groups (such as the illegal loggers) and the project timeframe is too short. Some of the challenges that need to be addressed in order to achieve effective project implementation include: the need to have a multistakeholders collaboration; development should be integrated and sustainable; and field staff need to have a permanent commitment to the community regardless of the project period.